Efektivitas Edukasi Menggunakan Media Leaflet pada Remaja Putri Tentang Personal Hygiene Saat Menstruasi di SMAN 5 Binjai - Sitepu, Jujuren; Febty Anggraini, Anisa; Hasibuan, Yusrawati (Journal of Comprehensive Science, 2025)
Low personal hygiene of young women during menstruation can invite attacks of various diseases. Based on an initial survey through interviews with 10 female students who had experienced menarche, at SMAN 5 Binjai, 8 of them had never received information about personal hygiene, and did not know proper and proper personal hygiene, while 2 of them applied personal hygiene during menstruation. The purpose of this study was to determine the effectiveness of education using leaflets as a medium for young women about personal hygiene during menstruation at SMAN 5 Binjai in 2023. This research is a Quasi-Experimental study designed with the One Group Pretest-Posttest Design Without Control, examining 60 adolescents daughters obtained through systematic sampling technique, and using a leaflet accompanied by a questionnaire that has been tested for validity and reliability as a research instrument. The research data was analyzed using the Paired T-Test. Through research, it was found that the average knowledge of personal hygiene during menstruation, the pretest result was 72.67, while the post test result was 89.33. The conclusion of this research is to find the influence of health promotion about personal hygiene during menstruation on the level of knowledge of young women.